Priprava prečiščenih besedil zakonov - Strle, Božo (Pravni letopis, 2010)
In 2002, the Rules of the National Assembly created the legal basis for preparing official consolidated texts of laws. From 2007 onwards, the new rules provide that after any change or addition to an existing law the Legislative and Legal Service of the National Assembly should prepare an unofficial consolidated text of the law to be published in electronic form on the National Assembly's website, while the official consolidated texts of the laws are now prepared only occasionally, on the basis of a decision adopted by the National Assembly on the proposal of its working body, the government or a parliamentary group. The article discusses the basic nomotechnical premises for the consolidation of the laws, where the main guideline remains the compliance consolidated with the text, adopted by the legislature.
Keywords: Slovenia; Slovenija; statute; zakoni; zakonodaja; zakonodajni postopek